Clinical Manifestations of Paederus Dermatitis: A Retrospective Cohort Study in a Tropical Country - Jiamton S. (2023)
Background: Paederus dermatitis (PD), or dermatitis linearis, is a skin reaction to a chemical substance called pederin from Paederus spp. Objective: To assess the clinical manifestations and seasonal variation of PD. Materials and Methods: The present study was a retrospective medical chart review of patients over 18 years of age diagnosed with PD attended by the Dermatology Clinic of Siriraj Hospital between January 2012 and January 2016. Results: Four hundred sixty-two patients with a median age of 35 years old were included in the present study. Most patients were female (77%). Lesions were found in exposed areas, especially extremities, and commonly manifested as erythematous patches and pustules in a linear arrangement or kissing lesions. Conclusion: Skin lesions with erythematous patches and pustules in a linear arrangement or kissing lesions are crucial for the diagnosis of PD. The PD cases were higher after the rainy seasons and flood events. However, the number of patients was not related to the season.